The Impact of Ecology on the Economic Development of Vinnytsia Region - SAMBORSKA, Oksana (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021DO - 10.14505//jemt.v12.2(50).09, 2021)
The problem of nature protection for the Vinnytsia region, most of the territory of which is experiencing almost uncontrolled intensive economic activity, is very relevant. Natural conditions and resources of Vinnytsia region are diverse and unique, the issue of their rational use is still insufficiently studied. Preservation of modern nature, increase of its riches, is impossible without research of available resources in the territory. Diagnosing minerals, the presence of rare plants, all available resources will help us to better understand the current situation and predict the future state of nature in the region, the possibility of its reconstruction not only by preserving but also creating new environmental facilities. Modern development of human activity is often harmful to the environment due to the growth of urban planning, industrial production, traffic. Therefore, there is pollution of water, air, soil, which negatively affects the health of the population, poses a threat to the environment, exacerbates environmental problems. Environmental pollution by industrial waste has a negative impact on the quality of natural resources, reducing their productivity or making them unusable, which reduces the economic potential of the region and the enterprise. The influence of the ecological factor on the production potential is manifested in the action of environmental pollution on the economic resources of the enterprise, reducing the efficiency of their reproduction and use. Such an impact is observed mainly at the stage of use and during the reproduction and development of production potential. The economic resources of the enterprise are exposed to the polluted environment in the form of industrial waste. As a result, the number of functioning resources decreases, their qualitative characteristics change. Reducing the number of resources and their quality indicators leads to a shortage of resources over time and to a change (decrease) in overall productivity. Thus, the real fund of time of equipment use decreases, labor productivity, equipment capacity, return of material and raw materials decreases (Lukyanikhin 2018).